The correlation of cashless banking and profitability in the banking industry in Bangladesh - Tanha, Moutusi; Alam, Md. Karimul; Mahmud, Sultan; Hossain, Shahadat; Alam, Murshed; Sabahel, Md. Al (Annals of Management and Organization Research, 2024)
Purpose: Cashless banking is an innovative banking policy that is gaining prominence in today's digital era of technological advancement. This study investigates the correlation between profitability of the banking sector and adoption of cashless banking in Bangladesh. Research Methodology: The profitability of the cashless banking industry in Bangladesh was measured using Return on Equity (ROE) and Return on Assets (ROA). Profitability is determined by the transaction volume of Mobile Financial Services (MFS), Automated Teller Machines (ATMs), bit cards, and internet banking fund transfers (IBFT). This study uses a multiple regression approach to analyze the association between a bank's profitability and cashless banking. The data used in this analysis were collected from the annual reports of the Central Bank of Bangladesh over a seven-year period. Results: The findings indicate that IBFT has a notable favorable influence on return on equity (ROE), whereas ATM and debit cards have major adverse impacts on ROE. Additionally, mobile financial services (MFS) and IBFT have a positive effect on return on assets (ROA), but debit cards have a negative effect on ROA in Bangladesh’s banking business. The data indicate that nearly all the components have either a positive or negative influence on ROA or ROE. Contribution: However, only IBFT has a positive and substantial influence on ROA and ROE. The results of this study have moderate importance for the regulatory bodies and stakeholders of both banks and non-bank financial firms as well as for academics and the government as a whole.